Quantum plasmonic nonreciprocity in parity-violating magnets - Arora, Arpit (2023)
The optical responses of metals are often dominated by plasmonic resonances, that is, the collective oscillations of interacting electron liquids. Here we unveil a new class of plasmons─quantum metric plasmons (QMPs)─that arise in a wide range of parity-violating magnetic metals. In these materials, a dipolar distribution of the quantum metric (a fundamental characteristic of Bloch wave functions) produces intrinsic nonreciprocal bulk plasmons. Strikingly, QMP nonreciprocity manifests even when the single-particle dispersion is symmetric: QMPs are sensitive to time-reversal and parity violations hidden in the Bloch wave function. In materials with asymmetric single-particle dispersions, quantum metric dipole induced nonreciprocity can continue to dominate at large frequencies. We anticipate that QMPs can be realized in a wide range of parity-violating magnets, including twisted bilayer graphene heterostructures, where quantum geometric quantities can achieve large values.